IMPROVING THE METHOD OF DETERMINING THE CALCIUM CONTENT IN MILK BY TITROMETRIC METHOD - Prylipko , T.M.; Bukalova, N.V.; Bogatko, N.M.; Lyasota , V.P. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
These studies are based on the task - to improve the method of determining the calcium content in milk bychanging the amount and concentration of reagents in the precipitation of protein and calcium in the form ofoxalate and its separation. The results obtained are solved by taking a portion of milk in the amount of 20.0-20.2 g and add a solution of trichloroacetic acid I with a mass concentration of 25% in the amount of 20.0-20.2cm3, shake vigorously for 2-3 seconds and leave stand for 20-22 minutes and then filter through ashless filterpaper to obtain a clear filtrate. Then 4.0–4.2 cm3 of clear filtrate is pipetted into a centrifugal cylindrical tubе with a rounded bottom with a capacity of about 30 cm3, graduated to 20 cm3, and 4.0–4.2 cm3 of trichloroaceticacid II solution with a mass concentration of 15% is gradually added., 1.5–1.6 cm3 of ammonium oxalatesolution with a mass concentration of 60%, 0.03–0.04 cm3 of methyl red solution with a mass concentration of0.1% and 1.5–1.6 cm3 of acetic acid solution with a mass concentration of 60% concentration of 22% .. The amount of potassium permanganate used is recorded to the nearest 0.01 cm3. In parallel with the determination, a control experiment is performed using 20.0–20.2 cm3 of distilled water instead of the tested milk sample.Studies have shown that the calcium content in various milk samples was within the norm according to current standards in Ukraine. The method is based on the determination of quantitative indicators of calcium content in milk by changing the amount and concentration of reagents during precipitation of proteins with trichloroacetic acid in the test sample during isolation of calcium oxalate filtrate and its separation by solutions of ammonium oxalate, methyl red, acetic acid, acetic acid, acetic acid in a water bath and titration with potassium permanganate until pink.